The Baltics and Bulgaria : Labor Markets in Hard-Peg Accession Countries. (IMF Staff Country Reports; Country Report ;, 2001)
The paper examines labor market developments in the four hard-peg European Union (EU) accession candidates during transition, with a view toward understanding the persistent high unemployment experienced in each country. Despite the significant levels of unemployment in all four countries, labor market developments suggest that the strongest and earliest reformers have had the best labor market performance as well. It is crucial that all four countries continue their policies aimed at encouraging investment and job creation. Accession to the EU will present challenges to labor markets.